Perbandingan Hukum Indonesia dan Malaysia dalam Kepemilikan Properti oleh Warga Negara Asing - Ligina Tesalonika; Handar Subhandi Bakhtiar; Atik Winanti (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Globalization has increased the interest of Foreign Nationals (WNA) in owning property in various countries, whether for residential purposes, holidays, or investment. Indonesia and Malaysia, as two Southeast Asian nations, have different regulatory approaches regarding property ownership by WNA. This research aims to analyze the legal provisions, identify similarities and differences in regulations, and evaluate their impact on the investment climate and legal protection for WNA in both countries. The research method used is comparative law, focusing on the legal basis, forms of ownership, limitations, and legal protection. The findings indicate that Indonesia tends to be protective of land ownership by foreign parties, strictly regulated through the Basic Agrarian Law (UUPA) No. 5 of 1960, which limits WNA to Right of Use (Hak Pakai) and Right to Build (Hak Guna Bangunan/HGB) with limited durations. In contrast, Malaysia adopts a more liberal and pro-investment approach, allowing WNA to own property as freehold or leasehold based on the National Land Code 1965 and the Malaysia My Second Home (MM2H) program. The implications of these differences are that Indonesia's restrictive policies may reduce the attractiveness of foreign investment due to legal ambiguity and limitations in secondary transactions. Meanwhile, Malaysia offers greater legal certainty and economic appeal through freehold ownership, despite social risks such as rising property prices. This study concludes that Malaysia has a more foreigner-friendly system for property ownership, while Indonesia maintains a cautious principle. It is suggested that Indonesia consider agrarian reforms that are more transparent and provide legal certainty that balances national interests with foreign investment attractiveness.